Respuesta :

Annder

Step-by-step explanation:

10. [-19-(-20) - (-34)] ÷ (-6)

= (-19+20+34) ÷ (-6)

= 35 ÷ (-6)

= -5.83

12. [-18 - (-66) -22] × 2

= [-18+66-22] × 2

= 26 × 2

= 52

tonb

Answer:

10. -35/6

12. 52

Step-by-step explanation:

A notation like - (-6) can be written as +6 ("two times minus is plus").

So your question 10. becomes:

(-19 + 20 + 34) / -6, which is more pleasant to the eye.

Further simplifying gives you 35 / -6 which you should write as -35/6.

The next question, same principle:

(-18 + 66 - 22) * 2 = 26 * 2 = 52